OP0121 Safety, Tolerability and Feasibility of Minimally Invasive Ultrasound-Guided Synovial Biopsy of Wrist and Metacarpophalangeal Joints - An Ultrasound Follow-Up Study. (15th July 2016) - Meric de Bellefon, L.; Durez, P.; Galant, C.; Avramovska, A.; Nzeusseu, A.; Lauwerys, B.; Houssiau, F.A.; Stoenoiu, M.S.
Abstract : Background: Synovitis is the common feature of patients suffering from inflammatory arthropathies (IA). The development of ultrasound (US)-guided synovial biopsy will enable synovial tissue collection from small joints and will facilitate molecular studies, thus improving the understanding of mechanisms of IA as small joints are frequently involved in these diseases. Objectives: To assess the safety, tolerability and feasibility to perform synovial biopsies from wrist and metacarpophalangeal (MCP) joints, using a minimally invasive US-guided technique in patients suffering from rheumatoid arthritis (RA), spondylarthropathies (SA) or undifferentiated arthritis (UA). Methods: Two target joints (TJ) were biopsied: wrist and MCP. Patients with at least one clinically swollen joint at these levels, suffering from RA, SA, or UA underwent a US examination. The TJ chosen for the biopsy was the joint with the most important inflammatory changes on gray-scale (GS) US. GS synovitis and power-Doppler (PD) activity were assessed by OMERACT scores, on the day of the biopsy, as well as 2 weeks (w), 6w and 6 months (m) after the biopsy. In addition, tendon tears, hematoma, paratenonitis and tenosynovitis were searched by US. Patient-reported outcomes (PRO) included a standard questionnaire given to all patients on the day of the biopsy as well as 1w, 2w, and 6w after the biopsy. Tolerability and the patient-reported willingness to repeat the procedure was assessed using the 5-point Likert scale. Results: Forty-one patients suffering from RA (27), SA (7) and UA (7) underwent US-guided biopsy of the wrists (20) and MCP (21) joints. A non-significant increase in pain was reported 24 h after the procedure. No difference in PRO of the biopsied joints was reported 2w and 6w after the biopsy, as compared to assessment before the biopsy. No infection or haemorrhage was observed after the biopsy. PRO did not differ significantly among patients suffering from RA, SA or UA. At the TJ, US scores tended to decrease 2w after the procedure. At 6w and 6m follow-up, no safety concerns were reported. Treatment response at the TJ was similar to the response of non-biopsied joints matched for the baseline US parameters. Conclusions: With the exception of study of Kelly et al (Ann Rheum Dis. 2015;74:611–6117), data on safety, tolerability, feasibility and PRO using the minimally invasive US-guided biopsy technique are lacking. In this work, we confirm that US-guided biopsy of wrist and MCP joints is feasible, safe and well tolerated by RA patients. At 2w, 6w and 6m follow-up, no safety concerns were reported. Furthermore, no differences in PRO between RA, SA and UA were observed. This technique is therefore a promising approach to assess the presence and persistency of synovial inflammatory processes in patients with early and refractory IA, and to facilitate patients stratification according to transcriptomic profiles. Acknowledgement: We acknowledge Pr C. Pitzalis and S. Kelly for giving us the opportunity to learn and further disseminate minimally invasive ultrasound-guided technique, and for fruitful discussions. Disclosure of Interest: None declared